2001
DOI: 10.1007/s00216-001-1116-7
|View full text |Cite
|
Sign up to set email alerts
|

Trace cobalt speciation in bacteria and at enzymic active sites using emission Mössbauer spectroscopy

Abstract: 57Co emission Mössbauer spectroscopy (EMS) allows the chemical state of cobalt, as influenced by its coordination environment, to be monitored in biological samples at its physiological (trace) concentrations. To draw attention to EMS as a valuable tool for speciation of cobalt in biocomplexes, the process of cobalt(II) metabolism in cells of the plant growth-promoting rhizobacterium Azospirillum brasilense Sp245 was investigated using EMS of 57CoII-doped bacterial cells. EMS measurements also showed 57CoII-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The yield of the stabilized 57 Fe III components in samples 1 and 2, resulting from aftereffects of the 57 Co→ 57 Fe nuclear transformation15, 16 (22–26%; see Table I) is much lower than for dilute rapidly frozen (80 K) aqueous 57 CoCl 2 solutions,15 reflecting a firm binding of parent 57 Co II in the intersubunit spaces of the GS oligomer4 to the organic ligands with higher electron–donor properties.…”
Section: Resultsmentioning
confidence: 97%
“…The yield of the stabilized 57 Fe III components in samples 1 and 2, resulting from aftereffects of the 57 Co→ 57 Fe nuclear transformation15, 16 (22–26%; see Table I) is much lower than for dilute rapidly frozen (80 K) aqueous 57 CoCl 2 solutions,15 reflecting a firm binding of parent 57 Co II in the intersubunit spaces of the GS oligomer4 to the organic ligands with higher electron–donor properties.…”
Section: Resultsmentioning
confidence: 97%
“…This technology allowed elements in biological samples to be monitored at their physiological (trace) concentrations. It showed that Co-57(II)-activated glutamine synthetase had 2 different Co (II) forms at its active sites (Kamnev et al 2002a).…”
Section: Production Of Enzymes and Enzymatic Studiesmentioning
confidence: 99%
“…(Macías-Vázquez and Calvo-de-Anta, 2009)], could lead to a deficiency of this essential trace element with a broad range of biological functions (Kamnev et al, 2002), including key steps in protein synthesis (Williams and Fraústo da Silva, 2000), N 2 fixation by Azotobacter and nitrate reductase activity, crucial for microbial NO 3 --N assimilation (Nicholas et al, 1962). Conversely, in rocky areas, where soil pH (6.14) under natural vegetation was already below the optimum range, the acidification triggered by C. edulis invasion (down to pH 4.97) was strong enough to significantly decrease Cu, Mg and Zn availability.…”
Section: Discussionmentioning
confidence: 99%